Pneumolysin Causes Neuronal Cell Death through Mitochondrial Damage - Braun, Johann S. (American Society for Microbiology, 2007)
Bacterial toxins such as pneumolysin are key mediators of cytotoxicity in infections. Pneumolysin is a pore-forming toxin released by Streptococcus pneumoniae, the major cause of bacterial meningitis. We found that pneumolysin is the pneumococcal factor that accounts for the cell death pathways induced by live bacteria in primary neurons. The pore-forming activity of pneumolysin is essential for the induction of mitochondrial damage and apoptosis. Pneumolysin colocalized with mitochondrial membranes, altered the mitochondrial membrane potential, and caused the release of apoptosis-inducing factor and cell death. Pneumolysin induced neuronal apoptosis without activating caspase-1, -3, or -8. Wild-type pneumococci also induced apoptosis without activation of caspase-3, whereas pneumolysin-negative pneumococci activated caspase-3 through the release of bacterial hydrogen peroxide. Pneumolysin caused upregulation of X-chromosome-linked inhibitor of apoptosis protein and inhibited staurosporine-induced caspase activation, suggesting the presence of actively suppressive mechanisms on caspases. In conclusion, our results indicate additional functions of pneumolysin as a mitochondrial toxin and as a determinant of caspase-independent apoptosis. Considering this, blocking of pneumolysin may be a promising cytoprotective strategy in pneumococcal meningitis and other infections.